Factorial Validity and Psychometric Properties of the Marital Scales–The Persian Version. Issue 4 (18th May 2016) - Fallahchai, Reza; Fallahi, Maryam; Park, Stacey S.
ABSTRACT: The aim of this study was to investigate the factor structure, convergent validity, and reliability of the Persian version of the Marital Scales. A sample of 627 participants (62.8% female, 37.2% male) were selected to participate from the available population. They completed the Socio-Demographic Characteristics Form and the Marital Scales. Results showed that internal consistency of this scale using Cronbach's alpha was .88 and the split-half coefficient was .86. Also, internal consistency of 3 main subscales (Intent to Marry, General Attitudes Toward Marriage, and Aspects of Marriage) was .80, .84 and .88, respectively, using Cronbach's alpha. The results of the factor analysis revealed that the Marital Scales is a multidimensional instrument with 10 distinct and related factors: intent to marry, positive attitudes, negative attitudes, fears and doubts, romance, respect, trust, finances, meaning, and physical intimacy. In general, the Marital Scales are a reliable and suitable instrument for assessing marital attitudes and expectations in Iran and other Persian-speaking countries.